2013
DOI: 10.1152/ajpgi.00225.2013
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus caseistrain Shirota protects against nonalcoholic steatohepatitis development in a rodent model

Abstract: Gut microbiota alterations are associated with various disorders. In this study, gut microbiota changes were investigated in a methionine-choline-deficient (MCD) diet-induced nonalcoholic steatohepatitis (NASH) rodent model, and the effects of administering Lactobacillus casei strain Shirota (LcS) on the development of NASH were also investigated. Mice were divided into three groups, given the normal chow diet (NCD), MCD diet, or the MCD diet plus daily oral administration of LcS for 6 wk. Gut microbiota analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 31 publications
5
60
1
1
Order By: Relevance
“…The ratios of each bacterial subgroup to total bacteria are shown in Fig. 5, B and C. Calculations of the relative abundance of each strain indicated that the ratios of lactic acid bacteria, such as Bifidobacterium and Lactobacillus, in feces were markedly lower in the MCD than in the NCD-fed group, whereas the ratios of the Bacteroides fragilis group and Enterococcus were higher, as we reported previously (31). Interestingly, the reduction in lactic acid bacteria in the MCD diet group was reversed in the MCD plus MC group.…”
Section: Suppressed MCD Diet-induced Nash Developmentsupporting
confidence: 81%
See 3 more Smart Citations
“…The ratios of each bacterial subgroup to total bacteria are shown in Fig. 5, B and C. Calculations of the relative abundance of each strain indicated that the ratios of lactic acid bacteria, such as Bifidobacterium and Lactobacillus, in feces were markedly lower in the MCD than in the NCD-fed group, whereas the ratios of the Bacteroides fragilis group and Enterococcus were higher, as we reported previously (31). Interestingly, the reduction in lactic acid bacteria in the MCD diet group was reversed in the MCD plus MC group.…”
Section: Suppressed MCD Diet-induced Nash Developmentsupporting
confidence: 81%
“…5). Levels of lactic acid bacteria, such as Bifidobacterium, were reportedly lower in NASH patients than in healthy subjects (43), and our group and others have shown prebiotics or probiotics such as lactic acid bacteria to ameliorate NASH development with decreased endotoxemia (23,31). Taking these prior reports into consideration, the favorable effect of MC might be attributable to increased lactic acid bacteria in the gut.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Four studies showed that mice fed an MCD diet for as few as 2 weeks but up to 7 weeks developed no change or had decreased levels of serum triglycerides, cholesterol, and glucose 27,37,38,44 . In contrast, in a study by Kim et al mice that were fed an MCD diet for 4 weeks developed elevated serum triglycerides and total cholesterol levels 22 .…”
Section: Methionine- and Choline-deficient (Mcd) Dietmentioning
confidence: 99%